Analysis of Digital Consumption Patterns of Digital Wallet Transaction Users in Indonesian Big Cities - Santoso, Agus Dwi; Wulandari, Retno Sawitri; Risdwiyanto, Andriya; Ahmad, Nazaruddin; Judijanto, Loso (Jurnal Sistim Informasi dan Teknologi, 2023)
This research aims to analyze how consumption patterns and transaction utilization have changed for young people when using e-wallet transactions. The research conducted by the author used a qualitative approach. In this research, the samples obtained by researchers used a purposive sampling method with a sample size of 100. This research used data collection techniques, including interviews, documentation, and a literature study. The raw data has been collected using interview and documentation data collection techniques, which the author then processes and analyzes. Based on research results, it was found that urban youth have currently experienced evolution or changes in the essence of consumption patterns. Consumption, which is actually a common life phenomenon that will never be replaced, has begun to shift in essence from the motivation of consumption to survive and fulfill needs to consumption to satisfy desires and lifestyle. The presence of digital transactions is here to meet these changes in consumption patterns. In a way, both of them have a mutual influence between consumption patterns, which are increasing in purchasing primary and secondary goods, and the high use of e-wallets, which is proven by the high circulation of money from year to year.